L’accès des aînés francophones aux foyers de soins en milieu minoritaire, un enjeu linguistique en santé et mieux-être - Forgues, Éric; Doucet, Michel; Noël, Josée. Guignard. (La Revue canadienne du vieillissement, 2011)
Access to long-term nursing homes by French-speaking seniors in minority situations is a very real problem. However, few studies have been conducted on this subject. We wanted to better understand this issue in New Brunswick while taking into account the language aspect. In this article, we will present the problem based on different issues encountered by Francophones in minority situations and by giving an overview of the studies conducted on French-speaking seniors in minority situations. We will then address the issue related to the rights of French-speaking senior to receive services in French in nursing homes by analyzing briefly the province’s legal requirements. Furthermore, we will present the regulatory framework of nursing homes in New Brunswick. Finally, we will provide a geographic analysis of existing New Brunswick nursing homes while taking into account the language aspect, the levels of service and the distribution of French-speaking seniors within the territory.

Mémoire sur l’accès aux soins de santé primaires au Nouveau-Brunswick - Société Santé et Mieux-être en français du Nouveau-Brunswick; Mouvement Acadien des Communautés en Santé du Nouveau-Brunswick Inc (2011)